Boosting solar-to-pyroelectric energy harvesting via a plasmon-enhanced solar-thermal conversion approach. (September 2022) - Li, Haitao; Wang, Huan; Li, Xiangming; Huang, Jiangchao; Li, Xuan; Boong, Siew Kheng; Lee, Hiang Kwee; Han, Jie; Guo, Rong
Abstract: Pyroelectric technology promises the potential transformation of waste heat into useful electrical energy to address the global energy and environmental crises. However, current designs suffer from low power output and the need for additional mechanical devices to drive pyroelectric conversion. Here, we introduce an efficient sunlight-triggered pyroelectric nanogenerator (S-PENG) by combining an Au@polyethylenimine modified graphene oxide (Au@rGO-PEI)-based solar-thermal layer with a PVDF pyroelectric layer. Our strategy integrates rGO's photothermal properties and Au nanoparticles' plasmonic effects to boost sunlight absorption for enhanced pyroelectric conversion. When S-PENG is irradiated with sunlight, solar-thermal temperature rapidly reaches ~68 °C in 30 s which is 23 °C higher than neat PVDF. The superior solar-thermal conversion consequently enables Au@rGO-PEI/PVDF to achieve a high power output of 940 μW/m 2 that is up to 35-fold better than other pyroelectric devices. By further incorporating S-PENG onto rotating windmill blades, we showcase a blade-type pyroelectric generator for direct solar energy harvesting without needing external light intensity adjustment device. This unique design functions efficiently at various outdoor environments (e.g. temperature, wind, and rain), notably achieving a high power output of 2700 μW/m 2 that can be stored in a capacitor (Voc, ~ 5.2 V, 300 s charging). Our work offers valuable insights for the design of next-generation S-PENG and their facile integration with other energy technologies (e.g. windmill) for concurrent electricity harvesting from different green energy sources. Graphical Abstract: Efficient sunlight-triggered pyroelectric nanogenerator (S-PENG) was fabricated by combining an Au@rGO-PEI-based solar-thermal layer with a PVDF pyroelectric layer. This unique design enables effective light-heat-electricity conversion without needing additional light adjustment device and can be integrated with windmill blades. ga1 Highlights: A novel high-performance sunlight-triggered pyroelectric nanogenerator(S-PENG) has been demonstrated. This S-PENG allows synergism of SPR and photothermal effects to boost the light absorption for higher power generation. Integration of S-PENG with windmill blades realizes efficient power generation without needing external shielding device.